IMPLEMENTASI MANAJEMEN HUMAS DALAM MENINGKATKAN CITRA SEKOLAH DI UPT SMK NEGERI 1 WAJO KECAMATAN TANASITOLO KABUPATEN WAJO - Panessai Sir; Muhammad Nasir; Sumarni; Juri Naswa Nathania; Nur Basira; Wulan Fabisian; Muh Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This studies is motivated by public relations managementin building school image based on four indicators, namely communication, propaganda building, establishing relationships with journalists, and advertising. The purpose of this study is to determine the implementation of public relations management in improving school image at UPT SMK Negeri 1 Wajo, Tanasitolo District, Wajo Regency. The type of research in this study is qualitative research using a descriptive approach. The subjects of this study are the School Principal, the Deputy Principal for Public Relations, one teacher, parents/guardians of students, and one alumnus. The object of this study is SMK Negeri 1 Wajo. The data collection techniques used in this study are observation, interviews, and documentation. The data analysis technique used in this study is descriptive analysis. The results of this study indicate that effective public relations management not only contributes to improving the school's image but also plays a crucial role in attracting prospective students to enroll. Thus, the success of public relations management can be one of the key factors in achieving broader educational goals.